The Role of Liquid Fuels Channel Configuration on the Combustion inside Cylindrical Mesoscale Combustor - Achmad Fauzan Hery Soegiharto; I. N. G. Wardana; Lilis Yuliati; Mega Nursasongko (Journal of Combustion)
This research intended to investigate combustion of liquid fuel in 3.5 mm inner diameter quartz glass tube mesocombustor, based on liquid film evaporation by using heat recirculation. The mesocombustor has a copper section for heating and evaporating the liquid fuel. In mesocombustor type A, the fuel was glided through the narrow canal in the copper wall while the air was glided through the axial of combustor. The flame could only be successfully stabilized in high-ratio equivalent ranging from ɸ  =1.1 to ɸ=1.6, due to the gap without combustion reaction caused by high air-fuel mixture over the limits of flame stability. Mesocombustor type B, which has annulus-shaped canal, could shift the flame stability from ɸ  =0.8 to ɸ  =1.2; however, it also narrowed the limits of flame stability due to the wall cooling. In mesocombustor type C, both liquid fuel and air were glided through the annulus-shaped canal in the copper wall to fix the fuel evaporation and air mixture. The flame of type C was successfully stabilized, from ɸ  =0.73 to ɸ  =1.48 wider than types A and B. The flame of type C mesocombustor is circle-shaped and fitted to cross section of mesocombustor, but it still has thin gap without any flames due to thermal quenching by the wall.